2019
DOI: 10.1155/2019/8748459
|View full text |Cite
|
Sign up to set email alerts
|

Association between Hemoglobin Glycation Index and NAFLD in Chinese Nondiabetic Individuals

Abstract: Purpose. Limited studies have preliminarily identified a positive association between nonalcoholic fatty liver disease (NAFLD) and hemoglobin glycation index (HGI). However, this association has not been fully established. We aim to investigate the association between NAFLD and HGI in Chinese nondiabetic individuals and to construct a risk score based on HGI to predict a person’s risk of NAFLD. Methods. After strict exclusion criteria, 5,903 individuals were included in this retrospective cross-sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…8,9,11 And in non-diabetic individuals, subjects with high HGI have a higher prevalence of non-alcoholic fatty liver disease, carotid atherosclerosis. 30,31 This study found a higher prevalence of vitamin D deficiency in patients with high HGI, and the HGI levels were inversely correlated with vitamin D.…”
mentioning
confidence: 55%
“…8,9,11 And in non-diabetic individuals, subjects with high HGI have a higher prevalence of non-alcoholic fatty liver disease, carotid atherosclerosis. 30,31 This study found a higher prevalence of vitamin D deficiency in patients with high HGI, and the HGI levels were inversely correlated with vitamin D.…”
mentioning
confidence: 55%
“… 32 HbA 1C may also vary due to biological differences among individuals, apart from hyperglycemic episodes. 33 Hyperglycemic episodes, in addition to the production of advanced glycation end-products also affect lipid metabolism and result in increased synthesis of TAGs that tend to deposit in various tissues of the body, including liver. TAG deposition in adipose tissue increases BMI, while in liver parenchyma it leads to fatty liver.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Cohen et al, reported that patients with NAFLD exhibited an increased plasma concentration of TG and TC ( Cohen and Fisher, 2013 ). Moreover, Hu et al (2019) suggested that Glu levels are related to NAFLD. Hb has also been found to be associated with NAFLD ( Jiang et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%